Strategi Jitu dan Efektif Menyelesaikan Soal Ujian Nasional Bahasa Inggris bagi Siswa Kelas XII SMK N 1 Bangkinang - Wandi Syahfutra; Siti Niah; Ardiya Ardiya; Pahmi Pahmi; Agung Prasetyo Wibowo; Prih Febtiningsih (LPPM UMRI, 2018)
Abstract The community service that has been done is aimed to give an idea and understanding of ​​the importance of English mastery and provide motivation for the participants in relation to English mastery. Furthermore, it is done in order to make the students easy to understand English, especially on basic materials with English learning methods that are related to students of SMK level using the concept of English for Specific Purpose (ESP) so that later students are able to do the English Language Test of National Examination well. Keywords: The community of public service, English for Specific Purpose, National Examination